Maturity shortening and market failure - Felix Thierfelder (Deutsche Bundesbank, 2012)
Motivated by the financial crisis of 2007-2009 several papers have provided explanations for why liquidity may dry up during market stress. This paper also looks at this issue but focuses on the question as to why the liquidity crunch was not uniform across maturities. As funding pressures were felt particularly severe at longer maturities, central banks saw a high need to provide longer-term liquidity. The paper asks what market failure central banks were addressing by intervening and whether they took on unwarranted credit risk by providing other than ultra-short liquidity. I propose a model in which financial firms' expectations about the availability of longer-term liquidity in the future may affect their investment decisions today, even though they have full access to borrowing at the onset. These investment decisions may in turn impact on the willingness of lenders to provide future long-term liquidity. Central banks, by promising to provide long-term liquidity, can rule out the inefficient rational-expectations equilibrium in which firms choose short-term projects or prefund a future potential liquidity need out of fear of not being able to receive long-term funding in the future. The model shows that firms of high credit quality may be particularly prone to choosing inefficient investment decisions for this very reason.
Keywords: D82; G21; G32; 330; Liquidity; Asymmetric Information; Debt maturity; Geldpolitik; Refinanzierung; Bankenliquidität; Laufzeit; Betriebliche Investitionspolitik; Zeit; Marktversagen; Asymmetrische Information; Theorie